The Krein method and the globally convergent method for experimental data - Karchevsky, Andrey L.; Klibanov, Michael V.; Nguyen, Lam; Pantong, Natee; Sullivan, Anders (Applied numerical mathematics, 2013)
Comparison of numerical performances of two methods for coefficient inverse problems is described. The first one is the classical Krein integral equation method, and the second one is the recently developed approximately globally convergent numerical method. This comparison is performed for both computationally simulated and experimental data.